Pengaruh Bermain Plastisin (Playdough) Terhadap Interaksi Sosial Anak Sekolah Dasar EBF. Al-Amal Baucau, Timor-Leste - Al-Fath, Roy Carlos; Rahayu Hastutiningtyas, Wahidyanti; Trishinta, Sirli Mardianna (Tribhuwana Tunggadewi University, 2023)
Social interaction problems often arise in elementary school children as a result of various events, one of which is the influence of social development in the surrounding environment. Efforts to improve social interaction skills in elementary school children are carried out by providing group playdough activities, aimed at developing social skills and fostering awareness of the existence of others and their social environment. This study aims to evaluate the impact of playing with plasticine (playdough) in groups on the social interactions of elementary school children. The research design uses a Pre-Experimental approach with a One-Group Pre-Post Test Design. The population involved in this research included 47 elementary school children at EBF. Al-Amal Baucau, Timor-Leste, with sampling carried out using the Simple Random Sampling method, so that 42 respondents were obtained as the research sample. Data was collected through observation sheets, and data analysis was carried out using the Marginal Homogeneity test using SPSS software. The research results showed that before receiving group playdough therapy, the majority of respondents (81.0%) had social interaction in the low category. After receiving therapy, the majority of respondents (64.3%) showed improvement to the moderate category. The Marginal Homogeneity Test produces a p-value of (0.000) (0.05), there is a significant influence of group playdough on the social interactions of elementary school children at EBF. Al-Amal Baucau, Timor-Leste. Future researchers are advised to explore other therapies that can further improve social interactions in elementary school children.